Important documents on security and diplomacy - Gupta, Arvind 1953-.; Chaturvedi, Mukul; Joshi, Akshay; India. National Security Council Secretariat (New Delhi Manas Publications published in collaboration with National Security Council Secretariat, 2005)
Sources on foreign relations, national security, and diplomacy.
Published in collaboration with National Security Council Secretariat.
Keywords: National security -- India -- Sources; India -- Foreign relations -- 1984- -- Sources